Swiss tourism in the age of climate change : vulnerability, adaptive capacity, and barriers to adaptation ... - Matasci, Cecilia (Lausanne, EPFL, 2012)
This thesis analyses the impacts of climate change on Swiss tourism. It looks in particular at the regional vulnerability, adaptation, and barriers that hinder this process. The final goal of the work is to make a contribution in bringing about a smoother shift to a more sustainable tourism sector better adapted to the changing conditions. In the first part, the thesis examines the regional vulnerability of Swiss tourism to climate change for a 2030-2050 time horizon in order to define which regions are most in need of taking action. We analyzed in particular the impacts generated by changes in climate suitability for tourism activities, snowpack reduction, glaciers melting, permafrost melting, natural hazards, water scarcity, and changes in landscape and scenic beauty. We selected 70 indicators describing the exposure, the sensitivity and the adaptive capacity of each of the 85 defined areas. We collected, weighted and assembled simulations on the possible impacts and statistical data covering the whole ...